Comparison of the Values Calculated in the Mathematical Models Used to Estimate the Amount of Solar Radiation Falling on a Horizontal Surface with the Measured Values of the City of Sabha - Sharif, Mohamed; Alowa, Mohamed (Journal of Pure & Applied Sciences, 2018)
In this paper we compared the calculated values using mathematical models (ASHRAE, Hotel, and Page) used to estimate the amount of total solar radiation incident on a horizontal surface with the measured values of the city of Sabha. The purpose is to obtain the best model whose calculated values are identical or close to the measured values. Because most models rely on constants that are directly related to the climatic conditions of the study site, we used the constants of the Sabha region and the modern corrective constants obtained from previous studies on some areas in the Sahara Desert similar to Sabha in climatic conditions and latitude angles. The equations of the three models were solved using a Fortran computer program. The results we obtained were compared with the measured values. We observed the effect of some clouds and dust in the atmosphere on measured readings for some months, which caused a difference between calculated values and measured values; we also observed that the values calculated by the model Page and the model correct Ashrae are approaching the measured values in most months of the year. In this study, we observed that the difference between measured values and calculated values is due to the lack of information on the solar radiation of the region that is sufficient to obtain accurate values. It should be noted that most of the constants found in scientific references were evaluated according to meteorological stations whose climatic conditions may be different from other climatic conditions.